Honour and violence : gender, power and law in southern Pakistan - Shah, Nafisa (New directions in anthropology, 2016)
"The practice of karo kari allows family, especially fathers, brothers and sons, to take the lives of their daughters, sisters and mothers if they are accused of adultery. This volume examines the central position of karo kari in the social, political and juridical structures in Upper Sindh, Pakistan. Drawing connections between local contests over marriage and resources, Nafisa Shah unearths deep historical processes and power relations. In particular, she explores how the state justice system and informal mediations inform each other in state responses to karo kari, and how modern law is iplicated in this seemingly ancient cultural practice."--Back cover